Sarcomatoid carcinoma of the colon: a rare diagnosis - Chundru, Swaroopa; Nandennavar, Manjunath; Karpurmath, Shashidhar V.; Angadi, Veerendra (International Journal of Research in Medical Sciences, 2021)
Report of a rare colon tumor treated successfully using conventional chemotherapy regimen.